ANALYSIS OF THE AGE DYNAMICS OF COMPETITIVE ACTIVITY IN ATHLETICS ALL-AROUND IN THE ASPECT OF SEXUAL DIMORPHISM - Netsvetaeva, E.S.; Borovaya, V.A.; Vrublevskiy, E.P.; Sevdalev, S.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the main directions of modernization of the training system for highly qualified freestyle swimmers based on a historiographic analysis of world records. Methods and structure of the study. The dynamics of world records in freestyle swimming at distances from 100 to 1500 m for men and from 100 to 800 m for women was analyzed, and methodological “finds” were identified based on the analysis of scientific and methodological literature on swimming. The study was conducted in 2021. Results and conclusions. In the period 1910-2020. there is an abrupt increase in record sports results in freestyle swimming. Basically, there is a conjugate change in these results in men and women at swimming distances of one energy supply zone, which indicates a methodological factor in changing sports results at this historical stage in the development of world swimming. The initial phase of rapid growth observed in the first decades of the 20th century is clearly marked, with a gradual slowdown in the growth of record results. In the second half of our century, a new acceleration in the growth of world records was revealed, which then gradually decreases. The relationship between the dynamics of world records of swimmers and the evolution of the methodology for training highly qualified athletes is traced. This pattern is observed in both men and women. Methodical "finds" appear, as a rule, every 20 years. The main prospects for improving the system of training elite swimmers: advanced training of coaching staff; the problem of finding outstanding performers; further intensification of training; modern logistics; regular monitoring of the athlete's condition; search for rational options; social guarantees for athletes and coaches.